Mondialisation, Clusterisation et recyclage colonial - Bernard Calas (EchoGéo)
What are the geographical effects in Africa of global economic integration? At a small scale, the Lake Naivasha (Kenya) case study shows that colonial exploitation and land use, post-colonial conversions, designation by globalized entrepreneurs of local assets as valuable resources converge to select spaces and convert them in a horticultural cluster. It is is made of 60 production units and up-stream and down streams activities, partly financed by alien investments. However, it is also united by a “small world” which merges localized and globalized actors. An emerging “territorrialisation” process is increasing this melting process. But colonial memory restricts these trends towards global distinction.